Bicentric evaluation of stabilizing sampling tubes for assessment of monocyte HLA‐DR expression in clinical samples. Issue 5 (12th June 2021) - Hamada, Sarah; Jeannet, Robin; Gossez, Morgane; Cour, Martin; Argaud, Laurent; Francois, Bruno; Daix, Thomas; Venet, Fabienne; Monneret, Guillaume
Abstract: Background: Diminished expression of human leukocyte antigen DR on circulating monocytes (mHLA‐DR), measured by standardized flow cytometry procedure, is a reliable indicator of immunosuppression in severely injured intensive care unit patients. As such, it is used as stratification criteria in clinical trials evaluating novel immunostimulating therapies. Preanalytical constraints relative to the short delay between blood sampling and flow cytometry staining have nevertheless limited its use in multicentric studies. The objective of the present work was to compare mHLA‐DR expression between whole blood samples simultaneously drawn in EDTA or Cyto‐Chex BCT tubes. Methods: In two university hospitals, mHLA‐DR was assessed in fresh whole blood from septic patients ( n  = 12) and healthy donors ( n  = 6) simultaneously sampled on EDTA and Cyto‐Chex BCT tubes. Staining was performed immediately after sampling and after blood storage at room temperature. Results: We confirmed that samples collected in Cyto‐Chex tube had substantially enhanced stability for mHLA‐DR results (48–72 h) over those collected in EDTA. On baseline values, despite good correlation between tubes ( r  = 0.98, p  < 0.001), mHLA‐DR expression was systematically lower with Cyto‐Chex BCT. Conclusion: The present reports confirms the potential of Cyto‐Chex BCT tubes to stabilize mHLA‐DR expression before staining and extends the work of Quadrini et al. [Cytometry B 2021;100:103‐114]. In centers without rapid access to flow cytometry facilities, it enables to tolerate delays in mHLA‐DR staining. However, a 30% gap exists between results obtained with EDTA and Cyto‐Chex BCT tubes. As current thresholds for clinical decisions were obtained with EDTA samples, further studies are needed to confirm clinical thresholds with Cyto‐Chex BCT tubes.